WNK1 in Malignant Behaviors: A Potential Target for Cancer? - Jung, Ji-Ung; Jaykumar, Ankita B.; Cobb, Melanie H. (Frontiers in Cell and Developmental Biology, 2022)
Metastasis is the major cause of mortality in cancer patients. Analyses of mouse models and patient data have implicated the protein kinase WNK1 as one of a handful of genes uniquely linked to a subset of invasive cancers. WNK1 signaling pathways are widely implicated in the regulation of ion co-transporters and in controlling cell responses to osmotic stress. In this review we will discuss its actions in tumor malignancy in human cancers and present evidence for its function in invasion, migration, angiogenesis and mesenchymal transition.